OPTIMIZATION OF NATIONALISM VALUES IN CHILDREN IN THE FAMILY THROUGH WORD PUZZLE GAMES IN PARI CITY, KEC PANTAI CERMIN KAB. DELI SERDANG - Salma Rozana; Rika Widya; Ranti Eka Putri (Proceeding International Seminar of Islamic Studies, 2023)
This research is motivated by the problem of low nationalism values in the younger generation seen in everyday life. Nationalism is an attitude that must exist and be instilled from an early age in students in order to nurture students to become good citizens, have knowledge, skills, and social care that are useful for themselves and society and the country. In line with this, at the elementary school stage, subjects are given that can support the cultivation of nationalism, namely PKN learning. Related to this problem, this study aims to optimize the value of nationalism in children through word puzzle games in Pari City, Perbaungan District, Serdang Bedagai Regency.